2015
DOI: 10.1096/fj.15-280388
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptor plays an important role in radiation‐induced dermal injury

Abstract: Ionizing radiation is a common therapeutic modality and following irradiation dermal changes, including fibrosis and atrophy, may lead to permanent changes. We have previously demonstrated that occupancy of A2A receptor (A 2A R) stimulates collagen production, so we determined whether blockade or deletion of A 2A R could prevent radiation-induced fibrosis. After targeted irradiation (40 Gy) of the skin of wild-type (WT) or A 2A R knockout (A2ARKO) mice, the A 2A R antagonist ZM241385 was applied daily for 28 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…In one study, macrophages expressing M2‐like markers have been linked to disease outcome in radiation‐induced renal fibrosis (50). Instead, an accumulation of T cells and no role for macrophages (51) or a contribution of macrophages had been observed in radiation‐induced skin fibrosis (30, 52), but without stating the macrophage phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, macrophages expressing M2‐like markers have been linked to disease outcome in radiation‐induced renal fibrosis (50). Instead, an accumulation of T cells and no role for macrophages (51) or a contribution of macrophages had been observed in radiation‐induced skin fibrosis (30, 52), but without stating the macrophage phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the role of adenosine and its receptors in fibrotic disease in vivo seems to largely depend on the tissue and the model investigated. Earlier reports revealed a critical role of ADORA2A signaling in dermal fibrosis induced, for example, by genetic loss of adenosine deaminase, systemic administration of bleomycin, and ionizing radiation, whereas ADORA2B activation was shown to play a major pathogenic role in the related models of pulmonary fibrosis (35, 51, 67, 68). These differences might be due to tissue‐specific expression patterns of adenosine receptors or other fibrosis‐modulating signaling molecules in resident cells or recruited immune cells, tissue‐specific damage responses, or both (67, 68).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, data enlighten the idea that adenosine, via preferential activation of A 2A receptors in fibroblasts, might be a key player in human subcutaneous connective tissue homeostasis and normal wound repair, while excessive scarring and dermal fibrosis may occur when this receptor is overexpressed ( Figure 6). For instance, adenosine A 2A receptor antagonists have been proposed to prevent radiation-induced dermal injury [50]. Disturbed adenosine homeostasis in the subcutaneous tissue may happen upon infiltration by ADA-bearing inflammatory cells and/or in situations occurring with increases in serum ADA levels, such as fibromyalgia and other chronic inflammatory conditions [51].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the beneficial effect of topical application of A 2A agonist on injured skin (Montesinos et al, 2002;Arasa et al, 2014); however, the mechanism at the basis is still unclear. However, there is also evidence that under pathologic conditions or following skin physical injury, such as radiation induced injury, A 2A receptor activation is responsible for fibrosis (Perez-Aso et al, 2016). Here, we show that systemic administration of A 2A agonist CGS21680 to rats inhibits paw inflammation induced by subcutaneous injection of carrageenan, increases FGF-2 dermal expression, and ameliorates skin cytoarchitecture.…”
Section: Discussionmentioning
confidence: 54%